2001
DOI: 10.1159/000049977
|View full text |Cite
|
Sign up to set email alerts
|

No Influence of Prednisolone on IGFBP-3 Proteolysis in Healthy Young Men

Abstract: Aims: The impact of growth hormone (GH) and prednisolone on the GH/insulin-like growth factor (IGF) axis with special emphasis on IGF binding protein-3 (IGFBP-3) proteolysis was studied in 8 healthy adults in a double-blind cross-over study with four periods: (1) placebo; (2) s.c. GH 0.1 IU/kg/day; (3) oral prednisolone 50 mg/day, and (4) co-administration of GH and prednisolone. Methods: Each treatment period lasted for 4 days followed by a washout period of 10 days. We measured IGF-I, IGF-II, IGFBP-1, IGFBP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…This is true for patients with anorexia nervosa (28,29), endstage renal failure (30), and poorly controlled type 1 diabetes (31), whereas GC treatment makes a notable exception. Despite its catabolic effects, GC excess is generally not accompanied by a suppression of the circulating IGF system (6,7,12,32). With the present data in mind, it appears that the ability of GC to inhibit serum IGF1 action is mediated through an inhibition of IGF1R phosphorylation rather than through changes in the circulating concentrations of free IGF1, total IGFs, or insulin.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This is true for patients with anorexia nervosa (28,29), endstage renal failure (30), and poorly controlled type 1 diabetes (31), whereas GC treatment makes a notable exception. Despite its catabolic effects, GC excess is generally not accompanied by a suppression of the circulating IGF system (6,7,12,32). With the present data in mind, it appears that the ability of GC to inhibit serum IGF1 action is mediated through an inhibition of IGF1R phosphorylation rather than through changes in the circulating concentrations of free IGF1, total IGFs, or insulin.…”
Section: Discussionmentioning
confidence: 54%
“…In this context, Lalou et al (34) demonstrated that proteolysis of IGFBP3 may yield fragments that possess no IGF1 binding activity but nevertheless retain the ability to inhibit IGF1 action in vitro. Whether this mechanism is operational following prednisolone treatment is, however, uncertain as prednisolone failed to induce IGFBP3 proteolysis in healthy adults (32). However, it could be speculated that prednisolone is able to induce inhibitory fragments from other IGFBPs than IGFBP3.…”
Section: Discussionmentioning
confidence: 99%